2018
DOI: 10.1111/add.14147
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects on adult drinkers of exposure to alcohol harm reduction advertisements with and without drinking guideline messages: experimental study

Abstract: Alcohol harm television advertisements increase intentions to reduce alcohol consumption among both low- and high-risk drinkers. The addition of low-risk drinking guidelines can enhance these effects for advertisements featuring long-term harms and improve estimates of both short- and long-term harmful drinking levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“… 28 32 In their evaluation of a mass media campaign focussed on the link between alcohol and cancer, Dixon and colleagues 28 found that intentions to reduce the amount of alcohol consumed increased by between 3.4 and 10.5 percentage points from before to after the campaign (at first and second follow-up, respectively) among those who consumed more than two drinks per day, compared with a 5.2 percentage point difference in intentions to reduce the amount of alcohol consumed on each occasion between those exposed to PH and SAPRO ads in the current study. Similarly, in Wakefield et al ’s study in which the effects of exposure to two PH ads about either the short-term harms or long-term harms of alcohol were compared with a non-alcohol related advertising control condition, comparable effect sizes for the measure of intentions to avoid alcohol completely were observed as in our comparison of PH and SAPRO ads (5.1 percentage points in the current study compared with 6.4 to 7.3 percentage points for long-term harm ads, and 6.2 to 6.3 percentage points for the short-term harm ads in the Wakefield et al study 32 ). These comparisons further increase our confidence that the small effects observed in this study have practical significance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 28 32 In their evaluation of a mass media campaign focussed on the link between alcohol and cancer, Dixon and colleagues 28 found that intentions to reduce the amount of alcohol consumed increased by between 3.4 and 10.5 percentage points from before to after the campaign (at first and second follow-up, respectively) among those who consumed more than two drinks per day, compared with a 5.2 percentage point difference in intentions to reduce the amount of alcohol consumed on each occasion between those exposed to PH and SAPRO ads in the current study. Similarly, in Wakefield et al ’s study in which the effects of exposure to two PH ads about either the short-term harms or long-term harms of alcohol were compared with a non-alcohol related advertising control condition, comparable effect sizes for the measure of intentions to avoid alcohol completely were observed as in our comparison of PH and SAPRO ads (5.1 percentage points in the current study compared with 6.4 to 7.3 percentage points for long-term harm ads, and 6.2 to 6.3 percentage points for the short-term harm ads in the Wakefield et al study 32 ). These comparisons further increase our confidence that the small effects observed in this study have practical significance.…”
Section: Discussionsupporting
confidence: 77%
“…Open access that is, motivation and intentions to behave in ways that reduce alcohol-related harm. Given the lacklustre performance of industry-funded harm reduction advertisements in previous limited research testing their effectiveness 5 21-23 and recent evidence that well-designed PH advertisements can increase motivation and intentions to reduce alcohol consumption, [28][29][30][31][32] we hypothesised that compared with PH advertisements, alcohol harm reduction advertisements developed by alcohol industry SAPROs would be less effective at generating motivation to reduce alcohol consumption and to behave responsibly in relation to alcohol (H1) and less effective at producing intentions to reduce alcohol consumption over the next week (H2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research suggests that drinkers would be receptive to and influenced by warning labels that inform them that alcohol is a carcinogen ( 45 47 ). In addition, mass media campaigns along the lines of those used in tobacco control have the potential to ensure consumers are informed of the harms associated with alcohol consumption ( 48 ). This is important in the face of ubiquitous alcohol advertising that depicts alcohol as a harmless product ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, although the current study included multiple potential confounders in the analysis, there may be others that were not addressed and that could have affected the results, such as religiosity (34). Fourth, we measured the association of health awareness with alcohol consumption and acknowledge the theoretical and research literature that notes the limited evidence of a direct association between knowledge and behaviour (13,35). However, given the understanding of the necessity of awareness, ahead of change in attitudes, as well as the contradictory results found in linking awareness of long-term alcohol effects to alcohol consumption in previous research, we sought to contribute to the literature in this area.…”
Section: Discussionmentioning
confidence: 99%